Penerapan Media Pembelajaran Kreatif untuk Membantu Siswa Mengeja dan Membaca pada Kelas 1 SDN Pattingalloang 1 di Kota Makassar - Jamaluddin, Jaja; Nisa Fisca Kirana, Andi; Yusuf, Faidah; Sahib, Nurfaizah; St. Muriati,; Asriviana, Risna; Faidah, Nur; Rosmawati,; Hasniah, St (KHIDMAH: Jurnal Pengabdian kepada Masyarakat, 2023)
The purpose of this service activity is to help students improve their reading and spelling skills. The implementation method used in this service is identifying the learning objectives to be achieved, using creative information boards to improve students' reading skills through creative learning media, and providing fun and interactive spelling exercises including the use of pictures, letters, and words that must be sorted or completed correctly to improve spelling skills, as well as encourage interest and motivation to learn. Based on the community service activities that have been carried out through the application of creative learning media in the form of letter boards, it turns out that it has a positive effect on letter recognition and the development of language skills in class 1 students at SD Negeri Pattingaloang 1 Makassar City. The use of these media helps create interactive, engaging, and effective learning experiences and helps students build a strong foundation in reading, spelling, and understanding language.